2001
DOI: 10.1016/s0736-0266(01)00051-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of chondrocyte adhesion to cartilage: role of β1‐integrins, CD44, and annexin V

Abstract: The initial adhesion of transplanted chondrocytes to surrounding host cartilage may be important in the repair of articular defects. Adhesion may position cells to secrete molecules that fill the defect and integrate repair tissue with host tissue. While chondrocytes are known to become increasingly adherent to cartilage with time, the molecular basis for this is unknown. The objective of this study was to investigate the role of (31-integrin, CD44, and annexin V receptors in chondrocyte adhesion to cartilage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 53 publications
5
53
0
1
Order By: Relevance
“…Low adhesion of chondrogenic cells to a substrate is expected at early stages after cell seeding [24,28]. We found that less than half of the seeded cells attached to the PLA scaffold, consistent with a previous study [27], and that a large number of cells were present on the incubation plates after one day of culture.…”
Section: Discussionsupporting
confidence: 91%
“…Low adhesion of chondrogenic cells to a substrate is expected at early stages after cell seeding [24,28]. We found that less than half of the seeded cells attached to the PLA scaffold, consistent with a previous study [27], and that a large number of cells were present on the incubation plates after one day of culture.…”
Section: Discussionsupporting
confidence: 91%
“…Upon binding, the calcium influx into chondrocytes is significantly stimulated (37). Second, there are some reports dealing with the interaction of annexin V and integrins (39,54). The interaction between FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…These layers of cartilage were either punched into smaller, 3.5-mm-diameter discs or used for cell isolation. Isolated chondrocytes were obtained by sequential enzymatic digestion (with 0.2% Pronase and 0.02% collagenase) of the cartilage slices from the 3 zones (32).…”
Section: Methodsmentioning
confidence: 99%